Radiation‐induced tumor immunity in patients with non‐small cell lung cancer. Issue 7 (22nd June 2019) - Lockney, Natalie A.; Zhang, Mei; Morris, Christopher G.; Nichols, Romaine Charles; Okunieff, Paul; Swarts, Steven; Zhang, Zhenhuan; Zhang, Bingrong; Zhang, Amy; Hoppe, Bradford S.
Abstract : Background: Radiation‐induced tumor immunity (RITI) influences primary tumor growth and development of metastases in preclinical cancer models with conventional radiotherapy. Antigen‐specific immune responses have also been shown for prostate cancer treated with radiotherapy. We examined whether RITI can be induced in patients with non‐small cell lung cancer (NSCLC) following proton radiotherapy. Methods: Pre‐ and post‐radiotherapy plasma samples from 26 patients with nonmetastatic NSCLC who received radiotherapy between 2010 and 2012 were evaluated by western blotting for IgG and IgM bands to assess RITI response to tumor antigens from lung cancer cell lines. Statistical analysis was used to evaluate any correlation among IgG or IgM and clinical outcomes. Results: Twenty‐one patients received proton therapy at 2 GyRBE/fraction ( n = 17) or 6–12 Gy/fraction ( n = 4); five received photon therapy at 2–2.5 GyRBE/fraction. Compared with the pretreatment baseline, new IgG or IgM binding was detected in 27% and 50% of patients, respectively. New IgG bands were detected in the 25–37 kD, 50–75 kD, and 75–100 kD ranges. New IgM bands were detected in the 20–25 kD, 25–37 kD, 37–50 kD, 50–75 kD, and 75–100 kD ranges. There was no difference in IgG and/or IgM RITI response in patients treated with photons versus protons, or in patients who received SBRT compared to standard fractionation ( P  > 0.05). There was no difference in overall survival, metastasis‐free survival, or local control based on IgG and/or IgM RITI response ( P  > 0.05). Conclusion: RITI can be induced in patients with NSCLC through upregulated IgG and/or IgM. RITI response was not associated with proton versus photon therapy or with clinical outcomes in this small cohort and should be examined in a larger cohort in future studies.